2015
DOI: 10.1016/j.neurobiolaging.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

L-type calcium channel blockers and substance P induce angiogenesis of cortical vessels associated with beta-amyloid plaques in an Alzheimer mouse model

Abstract: It is well established that L-type calcium channels (LTCCs) are expressed in astroglia. However, their functional role is still speculative, especially under pathologic conditions. We recently showed that the α1 subunit-like immunoreactivity of the CaV1.2 channel is strongly expressed in reactive astrocytes around beta-amyloid plaques in 11-month-old Alzheimer transgenic (tg) mice with the amyloid precursor protein London and Swedish mutations. The aim of the present study was to examine the cellular expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The primary goal of the current study was to unmask the molecular players that contribute to the dysregulation of astrocyte physiology during AD progression. It is well known in these cells that Aβ promotes calcium imbalance by mechanisms that involve endoplasmic reticulum activation and stress (Alberdi et al ., ), regulation of L‐type calcium channel expression (Daschil et al ., ), and calcium‐sensing receptor activation (Chiarini et al ., ). In addition to these activities, the glial cellular stress generated via NOX enzyme activities may contribute to leading glia‐mediated neurotoxicity in AD (Angelova & Abramov, ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of the current study was to unmask the molecular players that contribute to the dysregulation of astrocyte physiology during AD progression. It is well known in these cells that Aβ promotes calcium imbalance by mechanisms that involve endoplasmic reticulum activation and stress (Alberdi et al ., ), regulation of L‐type calcium channel expression (Daschil et al ., ), and calcium‐sensing receptor activation (Chiarini et al ., ). In addition to these activities, the glial cellular stress generated via NOX enzyme activities may contribute to leading glia‐mediated neurotoxicity in AD (Angelova & Abramov, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study took advantage of the OBSC system to explore mechanisms of pathological angiogenesis that are difficult to study in vivo. OBSCs are a potent, underused tool for exploring vascular phenotypes 23,36,37 with few prior studies seeking to explore this in combination with AD models 32,38 . Interestingly, the increased sprouting angiogenesis we observed in TgCRND8 OBSCs is more pronounced than we find in vivo at a similar age.…”
Section: Discussionmentioning
confidence: 99%
“…OBSCs represent a potent tool for exploring vascular phenotypes in a system that retains native cell populations and cytoarchitecture, Until now, whilst the OBSC model has been well established for studying angiogenic processes, (33), (34), (20), there were few studies seeking to explore this in combination with AD models. Slices from adult APP_SweDI mice have been found to express L-type calcium channels and substance P around amyloid plaques, pointing to altered angiogenesis at this key pathological site (35). Another study demonstrated that platelets from an AD mouse model damage healthy cortical vessels and induced Aβ accumulation when infused into wildtype OBSC vessels (28).…”
Section: Discussionmentioning
confidence: 99%